Continuity and change in forest restoration. A comparison of US ecology and forestry in the 1940s and 1990s. Issue 134 (August 2022) - Jönsson, Jimmy; Priebe, Janina; Mårald, Erland; Lundmark, Tomas
Abstract: Previous research has paid little attention to the multiple meanings of the concept of forest restoration. To gain a more comprehensive view of forest restoration, this paper compares the US forest restoration debate of the 1940s and 1990s, in the disciplines of ecology and forestry. The paper focuses on historical approaches to pasts and futures, and on "sociotechnical imaginaries" providing societal legitimacy to restoration ventures. Historical scientific papers constitute the paper's empirical sources. The analysis shows that, among ecologists and foresters, forest restoration of the 1940s was oriented towards efficiency and challenges such as wood demands during World War II, whereas restoration of the 1990s was oriented towards conservation and environmental challenges. The approaches of the 1940s′ ecologists and foresters seem motivated by a sociotechnical imaginary connecting forest restoration to societal progress, whereas the approaches of their 1990s′ counterparts seem motivated by a sociotechnical imaginary connecting forest restoration to the task of mitigating society's impacts . Based on the conclusions, it is argued that future research on forest restoration would benefit from comparing the idealized pasts of both yield- and conservation-oriented conceptions of forest restoration. Highlights: Historically, US ecologists' and foresters' approach forest restoration similarly. Historically, US aims of forest restoration have changed from yields to conservation. Research on forest restoration benefits from comparing restorers' view on the past.